Martindale : the complete drug reference. (London : Pharmaceutical Press, 2014)
Each entry includes Martindale identity number, titles and synonyms, CAS registry number, pharmacopoeias in which substances appear, atomic and molecular weights, chemical and physical strengths (solubility, storage, and temperature), adverse effects, and dosage.
Keywords: Pharmacopoeias; Pharmacopoeias; Pharmacopoeias